KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP LOYALITAS KARYAWAN - Muliati Muliati (AkMen JURNAL ILMIAH, 2020)
This study aims to examine the effect of transformational leadership, organizational culture and compensation on employee loyalty. The data were collected through a questionnaire distributed to the managers of PT. Bosowa Berlian Motor (BBM) as a population. The research sample used purposive sampling technique with the criteria of a manager who held a managerial position for at least 5 years when the research was conducted. The analytical method used is multiple linear regression through SPSS. The results of this study indicate that transformational leadership, organizational culture and compensation significantly affect employee loyalty.